Clinal variation along precipitation gradients in Patagonian temperate forests: unravelling demographic and selection signatures in three Nothofagus spp. - Soliani, Carolina (2020)
Context: Clinal genetic variation in natural populations could reflect either recent demographic history or the evolution of adapted genotypes along heterogeneous environments.Aims: We describe genetic variation patterns in three Nothofagus species of South American temperate forests, growing along steep rainfall gradients. Our hypothesis is that the selection pressure along this gradient reinforces the genetic structure previously shaped by Pleistocene climate oscillations. Methods: We screened variation along gradients at putative adaptive markers: candidate genes involved in response to drought, and EST-SSRs linked to drought stress genes. Genomic SSRs (gSSRs) were used to decouple the incidence of demographic events in the genetic structure.Results: Genetic diversity at SSRs agreed with the putative location of cryptic Pleistocene refugia in Nothofagus. In addition, each species showed different trends for nucleotide diversity at candidate genes. Unbiased heterozygosity significantly correlated with precipitation at EST-SSRs in N. nervosa. We found evidences of balancing selection and several SNPs departed from neutral expectations.Conclusions: Nothofagus genetic variability shows a strong imprint of demographic changes that reveals refugia location for the species during Pleistocene. This variability is modelled by environmental conditions across natural gradients, which impose selection pressure at genome regions related to stress response, providing clues about inter-specific differences in adaptive potential to water deficit.